The Role of PET Imaging Before, During, and After Percutaneous Hepatic and Pulmonary Tumor Ablation - McLoney, Eric D.; Isaacson, Ari J.; Keating, Patrick (Seminars in Interventional Radiology, 2014)
The combination of anatomic and metabolic information provided by positron emission tomography (PET)/computed tomography makes it an important imaging modality to be obtained in conjunction with percutaneous ablation of primary and secondary malignancies of the lungs and liver. Advantages include more accurate preprocedural staging to determine appropriate treatment options, intraprocedural guidance to target difficult-to-see lesions, and postprocedural detection of residual or recurrent disease. Future applications of PET include strategies for intraprocedural guidance with real-time determination of incompletely ablated tumor, and combined PET/magnetic resonance imaging before, during, and after ablation for greater sensitivity to detect disease.
Keywords: PET/CT; percutaneous ablation; hepatic tumors; pulmonary tumors; interventional radiology